SIMULASI PERBANDINGAN MANAGEMENT BANDWITDH MENGGUNAKAN TEKNIK QUEUE TREE DAN PCQ - Rahmat Novrianda Dasmen; Daud Rusdi; Rasmila (Fakultas Sains dan Teknologi-Universitas Buddhi Dharma, 2025)
The IT services at PSP Pusri Building are equipped with adequate internet network facilities. However, the distribution of bandwidth across the network is uneven, which leads to bandwidth contention among users and consequently slows down internet connections. This issue arises due to the absence of specific upload and download limits for each room, which affects network stability. Managing upload and download speeds is crucial for efficient data transmission, and bandwidth management is needed to address this problem. This study employs an action research methodology, which includes the stages of Diagnosis, Action Planning, Action Taking, Evaluating, and Specifying Learning. The research focuses on improving network performance by implementing bandwidth management. The Per Connection Queue (PCQ) tree and queue techniques are applied to organize data flow based on priority, ensuring better distribution of bandwidth across all rooms. The results of simulations conducted during the bandwidth management application show significant improvement. The implementation effectively reduces the congestion issues in each room by providing an equal distribution of bandwidth. By using these management techniques, the IT services in the PSP Pusri Building can ensure a more stable and efficient network, improving the overall internet experience for users. This approach not only resolves existing bandwidth issues but also serves as a model for future network improvements. The study highlights the importance of careful bandwidth management in maintaining optimal network performance, especially in environments with multiple users and varying data demands.